Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. Indah Logistik Cargo - Ika Tirta Candra Rini; Nurhadi Nugroho (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This study aims to find out whether there is an Effect of Service Quality on Customer Satisfaction. The population in this study is all customers of PT. Indah Logistics Cargo, of which 60 people were respondents in this study. This research uses primary data obtained by distributing questionnaires. The data analysis method in this research uses multiple linear regression, which is operated through the SPSS 26 program. The results showed that the t test for the service quality variable (X) affects customer satisfaction (Y). This can be seen from the calculation of 16,905 with a significance level of 0.000 < 0.05. Thus the hypothesis (H1) is accepted. For customer satisfaction variable (Y). This can be seen from the calculation of 1,391 with a singnificance rate of 0.000 < 0.05. Thus (Y) is accepted. Based on the F test, it is known that the singnification value is 0.000 or < 0.05. This shows that simultaneously the independent variable of servicequality (X) if applied together has a significant effect on customer satisfaction(Y). Based on the coefficient of determination test (R2), the value of the coefficient of determination in this study was 0.831 or 83.1%. This shows that 83.1% of customer satisfaction is influenced by the independent variables of service quality (X) and customer satisfaction (Y), while the remaining 16.9% is influenced by other variables that are not included in this research model.